OFICINAS TERAPÊUTICAS DE CONTOS COM CRIANÇAS EM SITUAÇÃO DE ABRIGAMENTO - Schonardie, Elisiane F.; Weiler, Adriane C. B.; Weeck, Angelica R.; Gonçalves, Marisa S.; Bandeira, Naiara A.; Trentin, Patrícia B.; Mlanarczyki, Renata d. S.; Cardoso, Vanessa d. S. (Salão do Conhecimento, 2013)
Resumo